Mechanical Properties of Muscles around the Shoulder in Breast Cancer Patients: Intra‐rater and Inter‐rater Reliability of the MyotonPRO. Issue 4 (4th November 2019) - Yeo, Seung Mi; Kang, Hyojeong; An, Soyeon; Cheong, Inyae; Kim, Yoon; Hwang, Ji Hye
Abstract : Background: Patients with breast cancer typically experience changes in the properties of muscles around the shoulder. However, there is no appropriate evaluation tool for these changes. Objective: The primary objective was to investigate the inter‐rater and intra‐rater reliability of muscle‐related parameters measured by the MyotonPRO, a myotonometer device. The secondary objective was to investigate differences in properties of muscle around the shoulder between the mastectomy side and the other side. Design: Cross‐sectional reliability study. Setting: Outpatient clinic in a tertiary care university‐affiliated hospital. Participants: Twenty‐two patients with breast cancer who underwent mastectomy. Methods: Muscle tone, stiffness, and elasticity of the pectoralis major (PM), sternocleidomastoid (SCM), and upper trapezius (UT) were measured using the MyotonPRO. Rater 1 performed two sets of measurements with a time interval of 30 minutes to determine intra‐rater reliability. Rater 2 performed measurements during the interval between the two sets of rater 1. Reliability was assessed using intraclass correlation coefficients (ICCs) and Bland‐Altman analysis. A paired t ‐test was used to compare muscle properties between the affected and unaffected sides. Main Outcome Measurements: Frequency (tone, Hz), stiffness (N/m), and decrement (elasticity). Results: Intra‐rater reliability was excellent (ICC > 0.75, 0.85‐0.98) for all parameters of the PM, SCM, and UT in the affected and unaffected upper limbs of patients with breast cancer. Inter‐rater reliability was fair to excellent for all parameters except unaffected PM elasticity (ICC = 0.34). There were significant differences in all parameters of the PM between the affected and unaffected sides. There were no significant differences in the parameters of the SCM and UT between the two sides. Conclusions: Our findings indicate that the MyotonPRO device is a feasible tool to quantify PM, UT, and SCM muscle properties (stiffness, tone, and elasticity) in patients with breast cancer. Level of Evidence: III.